DEVELOPING PRODIGY - Dr. Charul Jain; Yatharth Jain; Dr. S.M. Anas Iqbal; Sunakshi Tongia (International Journal For Research In Business, Management And Accounting, 2024)
An original research based on the learning pattern of children between the age of 4 to 8 years. The research is based on real time subject who is the first author and real time example of the research. Major observation and experimentation were conducted to create a working model.